The Conflicting Values in the Selected Work of the Lost Generation - Nýdecká, Gabriela (Univerzita Pardubice, 2024)
This bachelor's thesis explores the conflicting values in The Sun Also Rises by Ernest Hemingway as opposed to the established American values. It also delves into the historical and cultural background of the First World War and American values and mentions the Lost Generation.
Střet hodnot ve vybraném díle Ztracené generace
Keywords: American literature; Lost Generation; American values; disillusionment; Americká literatura; Ztracená generace; americké hodnoty; deziluze